2017
DOI: 10.1186/s12888-017-1373-4
|View full text |Cite
|
Sign up to set email alerts
|

In-patient costs of agitation and containment in a mental health catchment area

Abstract: BackgroundThere is a scarce number of studies on the cost of agitation and containment interventions and their results are still inconclusive. We aimed to calculate the economic consequences of agitation events in an in-patient psychiatric facility providing care for an urban catchment area.MethodsA mixed approach combining secondary analysis of clinical databases, surveys and expert knowledge was used to model the 2013 direct costs of agitation and containment events for adult inpatients with mental disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…While it is considered to be distinctly different to aggression [2], without timely assessment and management it can quickly escalate to a loss of personal control, aggression and violence [1] and result in injury to patients and staff [3,4]. Agitation can also lead to increased periods of hospitalisation [5] and episodes of readmission [6] resulting in increased health care costs [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…While it is considered to be distinctly different to aggression [2], without timely assessment and management it can quickly escalate to a loss of personal control, aggression and violence [1] and result in injury to patients and staff [3,4]. Agitation can also lead to increased periods of hospitalisation [5] and episodes of readmission [6] resulting in increased health care costs [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, only two studies contain information on the costs of agitation and aggression in psychiatric inpatients. Annual economic costs of aggression incidents were estimated to be €280535 and £179 million (€211 million (7)) in Spain and the United Kingdom, respectively (8,9). Both estimates are considered underestimates of the actual costs because indirect costs were not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature recommends verbal de-escalation and changes to patient environment as preferred first line treatment options followed by pharmacological intervention, with restraint as a last resort [ 4 ]. The impact of agitation on the healthcare system has been previously described; a 2013 analysis of Spanish Acute Impatient admissions identified that agitation increased the cost of an admission between €282 and €822, dependant on the interventions required to manage the episode [ 5 ]. However, the impact of agitation on costs to the healthcare system for community dwelling patients is not well known.…”
Section: Introductionmentioning
confidence: 99%